Transient hyphema associated with PRESERFLO® MicroShunt surgery using a double-step knife in patients with glaucoma - Rei Sakata; Makoto Aihara; Shiroaki Shirato (Scientific Reports)
Abstract To report the frequency of hyphema after PRESERFLO® MicroShunt (PMS) surgery using double-step knife in patients with glaucoma and to investigate its relationship with the tube insertion position. Glaucoma patients who underwent PMS surgery were reviewed. Hyphema was defined as visible hemorrhage in the anterior chamber. The insertion position of PMS was confirmed via gonioscopy. Patient backgrounds in the hyphema and non-hyphema groups were compared, and the course of visual acuity (VA), intraocular pressure (IOP), and time to resolution of hyphema were investigated. 65 of 66 eyes were eligible for consideration. Hyphema had occurred in 23 (35%) eyes. At the end of surgery, anterior chamber bleeding was observed under the microscope in 8 of 23 cases (35%). The tube fixation position was on the scleral spur (25 eyes), on the trabecular meshwork (27 eyes), on the Schwalbe line (10 eyes) and on the corneal side (3 eyes). There was no significant difference of the site of tube insertion between the two groups. All cases of hyphema spontaneously resolved within a few weeks, with stable IOP and recovered VA. It is worth noting that in PMS surgery using the double-step knife, hyphema may occur high frequency even if the tube insertion site is accurately positioned. Patients should be informed of the risk of hyphema before the surgery.